Fuctional outcome of intertrochanteric femur fracture after internal fixation with proximal femur nailing with medial entry portal - Dr. Hitesh L. Panchal,; Dr.Vraj B. Solanki,; Dr. Parth K. Macwan,; Dr. Aumkar H. Pandya,; Dr.Dev Y. Chavda,; Dr Saumya C. Shah, (The Bioscan, 2026)
Intertrochanteric fractures of the femur are common in the elderly population and are associated with significant morbidity and mortality if not treated appropriately. Early surgical fixation and mobilization are essential to restore function and reduce complications related to prolonged immobilization. This prospective study was conducted to evaluate the functional and radiological outcomes of intertrochanteric femur fractures treated with proximal femoral nailing (PFN). A total of 100 patients above 18 years of age with intertrochanteric femur fractures were included and managed surgically using PFN. Patients were followed up clinically and radiologically at regular intervals for a minimum period of six months. Functional outcome was assessed using the Harris Hip Score. The majority of patients belonged to the 60–79 year age group, with female predominance. Radiological union was achieved in most cases at a mean duration of 12 weeks. According to Harris Hip Score, excellent to good outcomes were observed in 85% of patients. Complications included superficial and deep infection, screw back-out, and varus collapse, with no cases of non-union or periprosthetic fracture. Proximal femoral nailing provided stable fixation, allowed early mobilization, and resulted in satisfactory functional and radiological outcomes. PFN is an effective and reliable method for the management of intertrochanteric femur fractures, particularly in elderly patients with osteoporotic bone. KEYWORDS: Intertrochanteric femur fracture; Proximal femoral nail (PFN); Proximal femur fracture; Internal fixation; Intramedullary nailing; Functional outcome; Harris Hip Score; Elderly patients; Osteoporotic Fractures; Evan’s classification; Stable and unstable fractures; Closed reduction; Early mobilization; Radiological union; Postoperative complications; Varus collapse; Screw back-out; Load-sharing implant; Minimally invasive fixation.